BUDAYA ORGANISASI DALAM UPAYA MENINGKATKANKINERJA KARYAWAN HARD ROCK HOTEL BALIDI KUTA-BALI - Agnes Putri Purba, - (2009)
Bali is icon of tourism in Indonesia.There are so many tourist destination in Bali such as Denpasar,Ubud,Kintamani,Lovina,Tulamben,Nusadua,Bedugul,Kuta,ect.Kuta is one of the famous and favorite tourist tourist destination becaouse there are so many entertaiment in there.Hard Rock Hotel Bali is one of place which provide 24 hours non stop entertaiment and music.Hard Rock Hotel Bali is "The Leading Entertaiment Hotel In Bali ".Hard Rock Hotel Bali Serve unique style and high quality subtance and have already fascinated and seduce million raving fans around the world that is the part of role management ,which build vision " Spread the spirit of Rock 'n Roll ",mission " Created Authentic experiences taht Rock!! ",in an environment which honors one of the most important culture phenomena of the 20th century : Rock 'n Roll Music.Operating values in Hard Rock Hotel Bali are Practice honesty, integrity and professional,Encourage everyone to maximize their potential,Take personal accountability for getting results ,Create brand excitement through innovation,Deliver kick-ass service,motto Hard Rock Hotel Bali are Love All- Serve All,Take Time To Be Kind,All Is One,Save The Planet.The vision, mission, operating values and motto are created " The Organization Culture in Hard Rock Hotel Bali ". It's related to increase an employee's performance in Hard Rock Hotel Bali, performance assessment are personal presentation ,administration skill, initiative/follow though ,human relation skill, communication skill, finance awareness ,responsibility, security and savety ,training and development of subordinate ,adherence to hotel company policies .Hard Rock Hotel Bali privileged to increase talented unique and enthusiastic employees as a part of the Hard Rock Hotel Bali team .Hard Rock Hotel Bali absolutely committed to the development professional growth of each and every one of employees in Hard Rock Hotel Bali.